2007
DOI: 10.1007/s00438-007-0311-4
|View full text |Cite
|
Sign up to set email alerts
|

RpoS regulation of gene expression during exponential growth of Escherichia coli K12

Abstract: RpoS is a major regulator of genes required for adaptation to stationary phase in E. coli. However, the exponential phase expression of some genes is affected by rpoS mutation, suggesting RpoS may also have an important physiological role in growing cells. To test this hypothesis, we examined the regulatory role of RpoS in exponential phase using both genomic and biochemical approaches. Microarray expression data revealed that, in the rpoS mutant, the expression of 268 genes was attenuated while the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 76 publications
(91 reference statements)
7
101
0
4
Order By: Relevance
“…osmY promoter activity depended on rpoS, and it was stimulated approximately threefold by Crl (Fig. 3A, null versus WT), consistent with results from previous studies (28). In the absence of Crl, the activity of the osmY promoter was slightly lower in the rpoS mutant strains than in the WT strain, but the promoter activity was still much higher than in the rpoS null strain (Fig.…”
Section: Identification Of Residues On the Surface Of σ Ssupporting
confidence: 90%
“…osmY promoter activity depended on rpoS, and it was stimulated approximately threefold by Crl (Fig. 3A, null versus WT), consistent with results from previous studies (28). In the absence of Crl, the activity of the osmY promoter was slightly lower in the rpoS mutant strains than in the WT strain, but the promoter activity was still much higher than in the rpoS null strain (Fig.…”
Section: Identification Of Residues On the Surface Of σ Ssupporting
confidence: 90%
“…The K42N mutant is deficient in s S protein induction during growth in poor media: Previous studies have demonstrated that s S is involved in regulating the efficiency by which bacteria utilize poor or limited carbon sources (Pratt and Silhavy 1998;Chen et al 2004;King et al 2004;Robbe-Saule et al 2007) as it downregulates several genes associated with energy metabolism Rahman et al 2006;Dong et al 2008). Thus, accumulation of s S in the cell elevates stress resistance while reducing the efficiency of carbon source utilization and conversely, at low levels of s S cells are more efficient at carbon source utilization but show reduced survival under stressful growth conditions (Ferenci and Spira 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the K42N mutant produced less s S protein under starvation conditions, resulting in an ability to grow faster than the wild type, conceivably because it remained in a s 70 -dependent growth phase rather than entering the stressstarvation phase. Moreover, lower levels of s S induce an increase in the metabolism of the TCA intermediates (Rahman et al 2006;Dong et al 2008). Dysregulation of s S in the K42N mutant was independent of genetic background since transfer of the resistance mutation to strain ATCC 14028 produced a similar conditionality during growth (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli, RpoS controls many genes involved in cellular metabolism and the stress response (Dong et al, 2008;Farewell et al, 1998;Loewen et al, 1998). Similarly, many B. burgdorferi genes encoding proteins with various putative physiological functions were induced by Rrp2, RpoN and RpoS; these genes included bb0251 (leuS), bb0777 (apt), bbk17 (adeC), bb0257 (cell division), bb0842 (arcB), bb0329 (oppA-2), bba34 (oppAV), bb0313 (ftsJ), bb0797 (mutS), bb0637 (nhaC-1), bbd20 (transposase), bb0646 (hydrolase), bb0728 (nox) and bb0729 (gltP) (Fraser et al, 1997).…”
Section: Genes Regulated By Rrp2 Rpon and Rposmentioning
confidence: 99%